A Facile Route to Fabricate Highly Anisotropic Thermally Conductive Elastomeric POE/NG Composites for Thermal Management. Issue 2 (23rd November 2017) - Feng, Chang‐Ping; Bai, Lu; Shao, Yan; Bao, Rui‐Ying; Liu, Zheng‐Ying; Yang, Ming‐Bo; Chen, Jun; Ni, Hai‐Ying; Yang, Wei
Abstract: Highly anisotropic polyolefin elastomer (POE)/natural graphite (NG) composites with high through‐plane thermal conductivity and excellent mechanical properties, in which NG sheet perfectly aligns along one direction, are prepared by two‐roll milling, hot compression, and mechanical cutting. The through‐plane thermal conductivity coefficient of POE/NG composites is markedly improved to be 13.27 W m −1 K −1 at an NG loading of 49.30 vol%. When the composite is used as a thermal management material, it shows excellent heat dissipating capability in the through‐plane direction, which is very important for thermal management in electronic applications. This effective method is highly probable to be widely used for the facile fabrication of polymer‐based thermal management materials. Abstract : Highly through‐plane thermally conductive polyolefin elastomer based composites filled with commercial nature graphite (NG) without any treatments are fabricated by a conventional melt‐mixing method of a two‐roll milling method. The as‐fabricated composites with NG flakes perfectly vertically aligning in the matrix reveal high through‐plane thermal conductivity (13.27 W m −1 K −1 ).